Genetic deletion of angiotensin AT2 receptor leads to increased cell numbers in different brain structures of mice - Bohlen und Halbach, Oliver von; Walther, Thomas; Bader, Michael; Albrecht, Doris (Regulatory peptides, 2001)
Angiotensin II (Ang II) is a potent vasoactive peptide and displays growth factor-like properties. Different high-affinity Ang II receptor subtypes (AT1A, AT1B and AT2) have been cloned. They are expressed in various brain structures. Additionally, it has been assumed that Mas could interact directly or indirectly with the renin-angiotensin system. The AT1 receptor mediates pressor and mitogenic effects of Ang II, whereas physiological function and signaling mechanisms of the AT2 receptor remain poorly understood. Recent reports have shown that Ang II could mediate apoptosis through AT2 receptors. Since the AT1A, AT2 and Mas knockout mice provide new tools for uncovering potential actions of Ang II, the cell number in different brain structures of male adult wild-type mice and mice deficient for AT1A, AT2 or Mas was evaluated to get more insight into the role of Ang II in central nervous system development. In nearly all investigated brain structures (cortex, hippocampus, amygdala, thalamus), the cell number was significantly higher in AT2-deficient mice in comparison to wild-type mice. To the contrary, in AT1A-deficient mice the cell number was significantly less than in controls in the lateral geniculate and the medial amygdaloid nucleus. However, cell numbers were not changed in Mas-knockout mice compared to their wild-types. These results show the contrary effects of both angiotensin receptors on cell growth and represent the first demonstration of their action on neuronal cell development evidenced in the adult mouse brain.